Arid zone ant communities of Western Australia - Gunawardene, Nihara (Curtin University, 2003)
This thesis is prepared in three parts; the first part is a study of the ant species of the southern Carnarvon Basin, which was undertaken in order to determine the patterns of ant species distribution in this arid zone area. The distribution patterns were looked at in terms of biogeographical regions and they demonstrated the transitional nature of this particular area. Recommendations to alter the border between the South-west Province and the Eremaean Province were supported. The next chapter of this thesis analysed ant species from long unburnt and burnt areas of three main vegetation types (two Triodia species grasslands and Acacia aneura woodlands) in the Gibson Desert Nature Reserve. This study was carried out to observe the recovery of ant populations after fire. The results provided further evidence that invertebrates are measurably impacted by fire in the arid zone. The final chapter is a comparison of these two arid zone studies with six other ant community studies from throughout Western Australia. It demonstrated the uniqueness of some arid zone sites as well as related each study to each other according to their ant communities.